Efectividad y seguridad de noradrenalina y etilefrina en hipotensión inducida por anestesia espinal en cesárea - Alvarez Vallejos, Luis Alberto (2019)
Objective: Define whether Noradrenaline is more effective and safe than Ethylephrine in the treatment of hypotension induced by spinal anesthesia in caesarean section. Materials and methods: An analytical, observational, prospective study was conducted in 90 pregnant women undergoing caesarean section who received treatment for arterial hypotension induced by spinal anesthesia. They were divided into two groups of 45 pregnant women. Group E received Ethylephrine bolus 1mg, group N received Noradrenaline bolus 8µg. Blood pressure, heart rate, vasopressor rescue numbers, fluids administered before and during caesarean section, intraoperative hemorrhage and Apgar scores were monitored. Statistical analysis was performed in SPSS® 22 and Microsoft Excel® 2010. Results: No significant differences were found in effective response to the vasopressor (p = 0.945), the time of maternal hypotension (p = 0.89) and the number of bailouts (p = 0.58). The incidence of tachycardia was statistically significant in the group that received ethylephrine (84.5% vs. 7.9%, RR = 72; CI = 3.81-193.87; p=0.00). The other outcomes studied did not show statistically significant difference. Conclusion: Ethylephrine and Noradrenaline are equally effective, but norepinephrine is safer in the treatment of hypotension induced by spinal anesthesia in caesarean section.